The association between SARS-CoV-2 infection with menstrual characteristics changes in China: a cross-sectional study - Yan Yi; Qiong Zhang; Jingpei Li; Shi Xie; Jing Fu; Yanping Li; Jing Zhao (Taylor & Francis Group, 2023)
Objective To evaluate the association between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection with menstrual changes, and analyze the possible related factors to menstrual changes. Methods A cross-sectional study based on online survey was conducted. Women who had been infected with SARS-CoV-2 completed the questionnaires voluntarily and were enrolled in this study. Participants were divided into menstrual change group and no menstrual change group, based on the presence or absence of menstrual changes. Results A total of 1016 women were enrolled, including 530 in the menstrual change group and 486 in the no menstrual change group. The three most common abnormalities were changes of menstruation cycles, menstruation flow and menstruation duration. Compared with the no menstrual change group, participants in the menstrual change group were significantly younger (32.55 ± 7.00 vs. 33.67 ± 7.39, p = .013), reported more severe symptoms with score ≥ 6 (32.1% vs. 21.1%), and had more severe mental health problems, showing nervous (22.6% vs. 17.3%, p = .009), anxiety (34.9% vs. 24.5%, p < .001), depression (14.7% vs. 8.2%, p = .003) and fear (10.8% vs. 6.4%, p = .011). Conclusions SARS-CoV-2 infection was associated with menstrual changes. The age, the severity of symptoms and mental health problems were related to menstrual changes.